(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to investigate the effects of sun dried organic apricot (SDOA) consumption on serum Total Cholesterol (TC), High-Density Lipoprotein-Cholesterol (HDL-C), Triglyceride (TG) and Total Antioxidant Capacity (TAC) levels in ratsMaterial and Methods: 120 males, 120 females rats were divided in to four groups according to their SDOA rates (1%, 2.5, 5 and 10) in chow (to be 24 rats in each gruop), and feding periods. At 120 days periods, the control group was fed with standard rat chow and the others were fed with 1%, 2.5, 5 and 10 SDOA supplemented diet. At the end of 30th, 60th, 120th days; 8 rats which each genders/ groups were sacrified by diethyl ether inhalation anesthesia, app. 8-10 mL blood samples were taken by intracardiac puncture and obtained serum samples were maintained at -20 ° C until the day of analysis.Results: After statistical analysis, TC levels of male rats; HDL-C levels of female rats increased in paralel with the feding process. Both TC and HDL-C levels of female rats were significantly higher than those of males. Although there were a significant decreases in TG levels of both sexes at the end of feding periods, there was no significant difference between TG levels of both genders.Conclusion: It is thought that increases in TC and HDL-C levels are caused by rats affected by long-term feding periods. In addition, the significant difference between TC and HDL-C levels of male and female rats are thought to be affected by gender-specific reference values. The decrease in TG levels in both sexes is considered to be due to the increased energy needs of rats as well as the effect of SDOA-added feeds.